2023
DOI: 10.5530/pj.2022.14.173
|View full text |Cite
|
Sign up to set email alerts
|

An In Silico Study to Explore the Role of EGFR in Ovarian Cancer

Abstract: The EGFR family of Receptor Tyrosine Kinases (RTKs) consists of 4 members (collectively referred to as the ErbB or HER family): EGFR itself, ErbB2 (HER2/Neu), ErbB3 (HER3) and ErbB4 (HER4). Like all RTKs, each ErbB receptor comprises a large extracellular region, a single spanning trans-membrane (TM) domain, an intracellular ABSTRACT EGFR is a tyrosine kinase receptor that has a role in the tumorigenesis of many types of solid tumors. Aberrantly phosphorylated or overexpressed EGFR is associated with cellular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 17 publications
0
0
0
Order By: Relevance
“…Finally, ClusPro 2.0 and BioLuminate 4.5 are molecular-docking tools that have been widely utilized in diverse biological systems due to their automated computational system and the quality of the predictions, which exceed 50% of the success rate compared to other tools [122][123][124][125]. Since the predictions in both programs were similar, it can be suggested that they are congruent; however, other tools could be used to confirm the results.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, ClusPro 2.0 and BioLuminate 4.5 are molecular-docking tools that have been widely utilized in diverse biological systems due to their automated computational system and the quality of the predictions, which exceed 50% of the success rate compared to other tools [122][123][124][125]. Since the predictions in both programs were similar, it can be suggested that they are congruent; however, other tools could be used to confirm the results.…”
Section: Discussionmentioning
confidence: 99%